If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -11 = 7x + 19 Reorder the terms: -11 + 2x = 7x + 19 Reorder the terms: -11 + 2x = 19 + 7x Solving -11 + 2x = 19 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -11 + 2x + -7x = 19 + 7x + -7x Combine like terms: 2x + -7x = -5x -11 + -5x = 19 + 7x + -7x Combine like terms: 7x + -7x = 0 -11 + -5x = 19 + 0 -11 + -5x = 19 Add '11' to each side of the equation. -11 + 11 + -5x = 19 + 11 Combine like terms: -11 + 11 = 0 0 + -5x = 19 + 11 -5x = 19 + 11 Combine like terms: 19 + 11 = 30 -5x = 30 Divide each side by '-5'. x = -6 Simplifying x = -6
| 1*x-2*y+3*z=-2 | | 7p^2=-30p-8 | | .25=.25-0.375 | | 3y-2=4y-7 | | 12x+27=3 | | G=d+k | | 6n+32=12n+2 | | 3(2x+1)=x | | 5p^2-p-18= | | 4r-4r=3 | | 6(x-4)-6x-10= | | 5z+9=4 | | .25x=3 | | 9(6+w)=8(3+w) | | (2x+7)+(18x-22)=180 | | x^3-2x^2=20 | | 10x+20-2x-12=4 | | 8x-3=7x+3 | | 180-2x=160 | | 2.25+1.8x=18 | | 4(z+8)=3z | | 2x+15y=-6 | | 3x-8=-2x-2 | | 1x-2y+3z=-2 | | 5y-3=107 | | (9x^3-6x^2+5x)+(6x^3+8x^2-13x)= | | 2x-8+15=13 | | 5(2x+1)=75 | | (1+w)(5w+2)=0 | | 2(4z-4)-4(z-3)= | | 4x+x+3x+2=90 | | 11x+14y=-22 |